Association between dengue cases with the characteristics of housing and knowledge about the disease - Agüero-Vega, Ader (2018)
Introduction: The objective of the present study was to determine if knowledge about dengue and housing characteristics are associated with dengue cases in two districts of Tingo María, Huánuco, during 2016. Methods: An analytical, case-control, retrospective longitudinal study was carried out, with a sample of 80 people. A total of 13 cases and 13 controls from the district of Luyando and 27 cases and 27 controls from the district of Rupa Rupa were evaluated by using the Excel and SPSS programs 19. Results: It was observed that the average age was 32 years with most cases of rural origin. In bivariate analysis, statistical significance was found with knowledge about dengue (P <0.02), type of garbage deposits (P <0.02) and presence of accumulated water in households (P <0.01). Conclusions: It is concluded that knowledge about dengue, the type of waste container, and the presence of water accumulated were factors related to cases of dengue.